Células tronco mesenquimais indiferenciadas no tratamento do trauma medular espinal de ratos Lewis - Fatima Maria Caetano Caldeira (2011)
The present study aimed at evaluating the effect of mesenchymal stem cells (MSC), from bone marrow, in rats with spinal cord injury (SCI). Thus, 61 adult male Lewis rats were distributed in 3 groups: sham (CN), placebo (PLA) and MSC (GCT). All animals underwent laminectomy of T12, whereas the animals in PLA and GGT underwent SCI performed with a 70g rod. After 14 days, the surgical site was exposed and for PLA and GCT, 2 L PBS and 1.5 x 105 MSC diluted in 2 L of PBS were administered at the injury epicenter, respectively. The experimental design was completely randomized. Neurological evaluation consisted of the BBB test and a descriptive scale adapted method, performed for 45 consecutive days. In the second, third and fifth weeks after inoculation, rats were euthanized, having their spinal cord collected for expression evaluation of BDNF, NT-3, Bcl-xL, Bax, and caspase-9 by RT-PCR. In the fifth week, the spinal cord was also assessed by immunohistochemical methods, using anti-NeuN, anti-eGFP, anti-GFAP, and anti-synaptophysin antibodies, as well as by the TUNEL technique. Neurological deficits were observed in the animals with injury, with difference between the medians of groups PLA and GCT (p <0.05). There was no difference on neurons identified by NeuN antibody (p> 0.05). The higher synaptophysin immunostaining intensity and the lower formation of apoptotic bodies for GCT was similar to CN (p> 0.05). PLA group showed a higher expression of Bax and caspase-9 (p <0.05). Thus, we conclude that the MSC preserved synaptophysin and propitiously affected apoptosis.